O trabalho docente nas instituições públicas de ensino superior: intensificação do produtivismo acadêmico na UFPA - FARIAS, Laurimar de Matos (Universidade Federal do Pará, 2012)
This study aimed to examine the implications brought about by the reform of the Brazilian state and the continuous reform of higher education and its consequences for teaching workers the IFES, aiming to uncover in this reform process resulted in the intensification of academic production of these professionals in the period 2000 to 2008, being the locus of this investigation the UFPA. The central focus is to examine how the accumulation of functions of an administrative, research and teaching influence the academic teachers / researchers, particularly those teachers who are holders of CNPq productivity Scholarship. Our way down this methodological work, based on their characteristics, such as a case study, which is a strategic and investigative allowing the unveiling of the complexities that permeate contemporary as a social phenomenon, in this case the high productivity in academic UFPA. Our approximations lead us to understanding that this new face is a state strategy of globalized nature that resizes the nation states to safeguard the interests of strengthening and maintaining the capitalist system that is naturalized worldwide. This scaling back political consequences, especially for public spaces that are structurally and economically affected by the absence state. Higher education is undergoing change in their social role, inevitably approaching the market from the reforms implemented. And the teachers / researchers in this context forms of career function overloading, versatility productive in that attention to the nature of evaluation criteria (entered in the CAPES and CNPq), cast his scientific work, whichever is the productivity factor inherent merit. Implying, in turn, the intensification and insecurity of these professionals.